Customer Loyalty During Pandemic: Understanding Loyalty Through the Lens of Online Ride Hailing Service Quality - Katon Pratondo; Zaid Zaid (Universitas Pendidikan Ganesha, 2021)
This research study aimed to research and analyze the influence of service quality on customer loyalty mediated by customer delight on online ride hailing industry in D.I. Yogyakarta. This research method used quantitative analysis involving data taken using a purposive sampling technique to collect the data from 128 online ride hailing customers in D.I. Yogyakarta with certain criteria as a sample. The sample data was then collected through a survey by using a questionnaire distributed to respondents. The data that had been obtained then analyzed through regression analysis, and path analysis by using the SPSS Statistics 25 program. The result of this study indicated that while service quality had positive influence on customer delight and customer loyalty. Customer delight also had a positive influence on customer loyalty, and at the same time played an important role in mediating the influence of service quality on customer loyalty. This study indicates that service quality plays an important and becomes the key role in influencing customer delight which is at the same time is an important factor in gaining customer loyalty in online ride hailing industry. Besides service quality, it turns out that customer Delight also has a positive influence on customer loyalty. and as a mediator, its role in mediating service quality on customer loyalty is also proven to be effective.